Analisis Kadar Air, Lemak, Protein dan Uji Organoleptik Pada Ikan Tuna (Katsuwonus pelamis, L) - John Dominggus Kalor; Betinia Susanti Runggamusi; Basa T Rumahorbo (Cenderawasih University, 2021)
Research Research on the analysis of water content, fat, protein, and organoleptic tests of grilled tuna and smoked tuna (Katsuwonus pelamis L) was carried out using experimental methods, which consisted of determination of water content, determination of fat content, determination of protein content, and organoleptic test. Data were analyzed quantitatively. The results obtained that the water content of asar tuna or grilled tuna is 60.85% and smoked tuna is 59.29%. The fat content of grilled tuna is 3.92% and smoked tuna is 1.45%. The protein content of grilled tuna obtained was 38.02% and smoked tuna was 53.87%. Meanwhile, the organoleptic test (preference) on the texture, taste, aroma, and color of grilled tuna and smoked tuna showed that smoked tuna had a higher level of preference than grilled tuna.Key Words: Water content; Fat; Protein; Organoleptic test; Katsuwonus pelamis